2005
DOI: 10.1111/j.1475-097x.2005.00632.x
|View full text |Cite|
|
Sign up to set email alerts
|

Physiological determinants of the variation in left ventricular mass from early adolescence to late adulthood in healthy subjects

Abstract: Normal LVM shows variation over a broad age range in both genders with a rise in adolescence and subsequent decline with increasing age in adulthood despite an increase in SBP and physical activity. BSA, age, and gender were found to be major contributors to the variation in LVM in healthy adults, while haemodynamic factors, exercise, and wall stress were not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
(19 reference statements)
2
18
1
Order By: Relevance
“…The reason for the elevated LVM CoR in the LVH cohort is somewhat less explainable, although may have been in part due to poor differentiation of hypertrophic myocardial borders and errors associated with identifying the enlarged papillary muscles and trabeculae often associated with the endocardial border. Recent studies have also identified a dependency of LVM variation with age [14] and gender [15]. Neither variable was specifically controlled for in this study and as such might influence the magnitude of the mean values obtained for each clinical cohort, but neither parameter were expected to influence the repeatability parameters significantly.…”
Section: Discussionmentioning
confidence: 97%
“…The reason for the elevated LVM CoR in the LVH cohort is somewhat less explainable, although may have been in part due to poor differentiation of hypertrophic myocardial borders and errors associated with identifying the enlarged papillary muscles and trabeculae often associated with the endocardial border. Recent studies have also identified a dependency of LVM variation with age [14] and gender [15]. Neither variable was specifically controlled for in this study and as such might influence the magnitude of the mean values obtained for each clinical cohort, but neither parameter were expected to influence the repeatability parameters significantly.…”
Section: Discussionmentioning
confidence: 97%
“…An interesting finding of the present study is related to target organ damage in adolescent female and male hypertensives. Increased LVMI in male hypertensive teenagers compared with females has to be evaluated with caution, as previous studies have also suggested that LVMI is increased in males without hypertension as well, 22 and the difference in LVMI between hypertensive boys and girls might also be related to gender differences in hypertension. 7 This finding was not supported by our study, however, as we found no differences in LVMI of normotensive girls and boys.…”
Section: Discussionmentioning
confidence: 98%
“…Another critical point is that despite a comparable DM duration, subjects with periodontitis tend to be older than the Controls. LV mass has been found to be elevated in adolescence and subsequently decreased with aging in adulthood . It is therefore possible that there may be a sequential change in LV wall thickness from hypertrophy to wasting along with aging.…”
Section: Discussionmentioning
confidence: 99%